Contribution of liver alcohol dehydrogenase to metabolism of alcohols in rats. (5th June 2015) - Plapp, Bryce V.; Leidal, Kevin G.; Murch, Bruce P.; Green, David W.
Highlights: Rat liver alcohol dehydrogenase is active on a wide variety of alcohols. Rats eliminate primary alcohols and diols with zero order kinetics. Rats metabolize secondary alcohols to the ketones with first order kinetics. Alcohol dehydrogenase is a major contributor to metabolism of various alcohols. Elimination of alcohols is limited by alcohol dehydrogenase and unknown factors. Abstract: The kinetics of oxidation of various alcohols by purified rat liver alcohol dehydrogenase (ADH) were compared with the kinetics of elimination of the alcohols in rats in order to investigate the roles of ADH and other factors that contribute to the rates of metabolism of alcohols. Primary alcohols (ethanol, 1-propanol, 1-butanol, 2-methyl-1-propanol, 3-methyl-1-butanol) and diols (1, 3-propanediol, 1, 3-butanediol, 1, 4-butanediol, 1, 5-pentanediol) were eliminated in rats with zero-order kinetics at doses of 5–20 mmol/kg. Ethanol was eliminated most rapidly, at 7.9 mmol/kg h. Secondary alcohols (2-propanol- d 7, 2-propanol, 2-butanol, 3-pentanol, cyclopentanol, cyclohexanol) were eliminated with first order kinetics at doses of 5–10 mmol/kg, and the corresponding ketones were formed and slowly eliminated with zero or first order kinetics. The rates of elimination of various alcohols were inhibited on average 73% (55% for 2-propanol to 90% for ethanol) by 1 mmol/kg of 4-methylpyrazole, a good inhibitor of ADH, indicating a major role for ADH in the metabolism of the alcohols. The Michaelis kinetic constants from in vitro studies (pH 7.3, 37 °C) with isolated rat liver enzyme were used to calculate the expected relative rates of metabolism in rats. The rates of elimination generally increased with increased activity of ADH, but a maximum rate of 6 ± 1 mmol/kg h was observed for the best substrates, suggesting that ADH activity is not solely rate-limiting. Because secondary alcohols only require one NAD + for the conversion to ketones whereas primary alcohols require two equivalents of NAD + for oxidation to the carboxylic acids, it appears that the rate of oxidation of NADH to NAD + is not a major limiting factor for metabolism of these alcohols, but the rate-limiting factors are yet to be identified.